СТІЙКОСТІ ЛІНІЙНИХ СИСТЕМ ДИФЕРЕНЦІАЛЬНИХ РІВНЯНЬ З ВИПАДКОВИМИ СТРИБКОПОДІБНИМИ ЛІНІЙНИМИ РОЗВ’ЯЗКАМИ В ГІЛЬБЕРТОВОМУ ПРОСТОРІ - Nikitin, Anatoliy Volodymyrovych (Кам'янець-Подільський національний університет імені Івана Огієнка, 2013)
The conditions of stability in the middle and in the mean square solutions of stochastic differential equations with random perturbations in Hilbert spaces are obtained.